Das Museum of Modern Art New York zu Gast im Kunstmuseum Bern und Museum Ludwig Köln. - Kunstmuseum Bern, Bern; Museum Ludwig, Köln (Bern : Kunstmuseum Bern, 1979)
Albers, Josef ; Avery, Milton ; Bailey, Malcolm ; Bourgeois, Louise ; Calder, Alexander ; Close, Chuck ; Davis, Stuart ; Dine, Jim ; Estes, Richard ; Ferber, Herbert ; Flavin, Dan ; Francis, Sam ; Frankenthaler ; Helen ; Gorky, Arshile ; Gottlieb, Adolph ; Guston, Philip ; Held, Al ; Hofmann, Hans ; Irwin, Robert ; Johns, Jasper ; Kelly, Ellsworth ; Kline, Franz ; de Kooning, Willem ; Krasner, Lee ; etc.
Das Museum of Modern Art New York zu Gast im Kunstmuseum Bern und Museum Ludwig Köln : Amerikanische Kunst des 20. Jahrhudnerts, Kunstmuseum Bern, 16.2. - 16.4.1979 / Museum Ludwig Köln, 19.5. - 16.7.1979
boek